Radioimmunotherapy in colorectal cancer treatment: present and future - Shi, Jingyi; Sun, Zhuang; Gao, Zhaoya; Huang, Dandan; Hong, Haopeng; Gu, Jin (Frontiers in Immunology, 2023)
Colorectal cancer (CRC) is a deadly form of cancer worldwide. Patients with locally advanced rectal and metastatic CRC have a poor long-term prognosis, and rational and effective treatment remains a major challenge. Common treatments include multi-modal combinations of surgery, radiotherapy, and chemotherapy; however, recurrence and metastasis rates remain high. The combination of radiotherapy and immunotherapy (radioimmunotherapy [RIT]) may offer new solutions to this problem, but its prospects remain uncertain. This review aimed to summarize the current applications of radiotherapy and immunotherapy, elaborate on the underlying mechanisms, and systematically review the preliminary results of RIT-related clinical trials for CRC. Studies have identified several key predictors of RIT efficacy. However, current studies have limitations. Summarily, rational RIT regimens can improve the outcomes of some patients with CRC, but current study designs have limitations. Further studies on RIT should focus on including larger sample sizes and optimizing the combination therapy regimen based on underlying influencing factors.